EXISTENCE OF NONLINEAR NEUTRAL IMPULSIVE INTEGRODIFFERENTIAL EVOLUTION EQUATIONS OF SOBOLEV TYPE WITH TIME VARYING DELAYS - Radhakrishnan, B.; Mohanraj, A.; Vinoba, V. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2013)
In this paper, we prove the existence of solutions for nonlinear neutral impulsiveevolution integrodifferential equations of Sobolov type with time varying delays. The results are obtained by using semigroup theory and the Monch's fixed point theorem.An application of the same problem is discussed. An example is provided to illustratethe theory.